PENGARUH PEMANFAATAN GEOGRAPHIC INFORMATION SYSTEM (GIS) TERHADAP PEMAHAMAN PEMETAAN SOSIAL PESERTA DIDIK SEKOLAH DASAR - Mitia Sismi; Marinda Siska; Leony; Serpadeni; Sumanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of Geographic Information System (GIS) utilization on social mapping understanding among fifth-grade students at SDN 78/III Lubuk Nagodang. GIS is a digital map-based technology that enables interactive visualization, analysis, and interpretation of spatial data, thus having significant potential to enhance students' social mapping abilities. Social mapping understanding in the context of elementary education encompasses the ability to recognize population distribution, identify regional resources, and understand the relationship between geographical conditions and community social life. This study used a quantitative method with a quasi-experimental design in the form of a one group pre-test post-test design. The population and sample of the study were all 12 fifth-grade students at SDN 78/III Lubuk Nagodang, selected using a saturated sampling technique. The research instrument consisted of a social mapping understanding test comprising 25 validated and reliability-tested multiple-choice questions. Data analysis was conducted using a paired sample t-test to determine differences in understanding before and after the treatment. The results showed a positive and significant effect of GIS utilization on social mapping understanding, with t-count = 8.74 > t-table = 2.201 at a significance level of 0.05, and an increase in the average score from 58.33 to 82.50 (N-Gain = 0.58, moderate category). These findings imply that GIS integration in social studies learning has great potential to enhance the spatial literacy and social mapping understanding of elementary school students.